2003
DOI: 10.1902/jop.2003.74.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Diabetes Mellitus: The Role of Tumor Necrosis Factor‐α in a 2‐Way Relationship

Abstract: It is generally accepted that obesity is associated with many other multiple-risk factor syndromes such as hypertension, hyperlipidemia, type 2 diabetes mellitus, and periodontal disease. The number of obese people is increasing rapidly in both western and eastern countries. Adipocytes in the adipose tissues of obese people produce large quantities of biologically active molecules such as leptin, an important molecule regulating energy expenditure and body weight. Therefore, adipocyte-derived active molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
182
1
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(196 citation statements)
references
References 25 publications
2
182
1
11
Order By: Relevance
“…In older Japanese subjects, periodontitis has also been shown to become worse along with worsening eGFR category (classified as >60, 30–59, and <29 ml/min −1  1.73 m −2 ) (Iwasaki et al, 2012). Furthermore, several studies have suggested a bidirectional relationship between glycemic control and periodontal disease (Okada et al, 1996; Nagasawa et al, 2010; Nishimura et al, 2003). It is generally accepted that elevated glucose levels promote the pathophysiology of periodontitis (Preshaw & Bissett, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In older Japanese subjects, periodontitis has also been shown to become worse along with worsening eGFR category (classified as >60, 30–59, and <29 ml/min −1  1.73 m −2 ) (Iwasaki et al, 2012). Furthermore, several studies have suggested a bidirectional relationship between glycemic control and periodontal disease (Okada et al, 1996; Nagasawa et al, 2010; Nishimura et al, 2003). It is generally accepted that elevated glucose levels promote the pathophysiology of periodontitis (Preshaw & Bissett, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by destruction of connective tissue, the periodontal ligament, and alveolar bone, leading to a significant increase of systemic exposure to bacteria (Okada et al, 1996). Many investigators have suggested a two‐way relationship between diabetes and periodontitis (Nagasawa et al, 2010; Nishimura et al, 2003; Preshaw et al, 2012). Interestingly, it has been reported that periodontal infection shows a positive correlation with endothelial dysfunction (Tonetti et al, 2007) and that infection with Porphyromonas gingivalis increases endothelial injury in obese mice (Ao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Presence of this cytokine may contribute to the heightened state of inflammation that is observed in diabetic subjects [14,15].…”
Section: Non-surgical Periodontal Therapy (Srp)-effect On Glycaemic Cmentioning
confidence: 99%
“…La periodontitis y los trastornos endocrinos, como la diabetes mellitus, abarcan una respuesta caracterizada por inflamación y secreción de citoquinas que destruyen el periodonto, causando alteraciones sistémicas (15,16).…”
Section: Introductionunclassified